O PARADIGMA DE EDUCAÇÃO RURAL DA ORGANIZAÇÃO DAS NAÇÕES UNIDAS PARA ALIMENTAÇÃO E AGRICULTURA - FAO NO BRASIL: FUNDAMENTOS CONCEITUAIS, POLÍTICAS DE DESENVOLVIMENTO E CONTRADIÇÕES IDEOLÓGICAS - DALMAZ, DAYANE SANTOS SILVA (2016)
This study aims to analyze the concept of education in rural development proposal Food and Agriculture Organization - FAO, UN specialized agency, which since its inception in 1945, has developed partnership in technical cooperation projects in Brazil . Its main projects in Brazil are linked to rural development, food security and nutrition, agricultural production, sustainable development and rural education, the subject of this study. In this sense, the issue focuses on the design of rural education FAO, that is, its conceptual foundations and the present ideological contradictions in the rural development proposal for peripheral countries, especially to Brazil, from 2005, year in which the FAO has established a partnership with MEC, laid the foundation of the "new perspective" of rural education for sustainable development: the formation of abilities and skills to rural areas. That is, the formation of human and social capital to the new demands of domestic and international capital. For this research we used as a methodology to analyze documents produced by the Agency between the years 1945 and 2005, in which the concepts of education and rural development were analyzed. In addition, a literature search was conducted in the light of the intellectuals of dialectical historical materialism, sought to explain the conceptual and ideological contradictions in the FAO proposal.